Unleashing quantum algorithms with Qinterpreter: bridging the gap between theory and practice across leading quantum computing platforms - Wilmer Contreras-Sepúlveda; Braulio Misael Villegas-Martínez; Sandra Gesing; José Javier Sánchez-Mondragón; Juan Carlos Sánchez-Pérez; Claudia Andrea Vidales-Basurto; J. Jesús Escobedo-Alatorre; Angel David Torres-Palencia; Omar Palillero-Sandoval; Jacob Licea-Rodriguez; Néstor Lozano-Crisóstomo; Julio César García-Melgarejo; et al. (PeerJ Computer Science)
Quantum computing is a rapidly emerging and promising field with the potential to transform various research domains including drug design, network technologies, and sustainable energy solutions. Due to the inherent complexity and divergence from classical computing, several major quantum computing libraries have been developed to implement quantum algorithms, namely IBM Qiskit, Amazon Braket, Cirq, PyQuil, and PennyLane. These libraries enable quantum simulations on classical computers and execution on corresponding quantum hardware, such as Qiskit programs on IBM quantum computers. Despite the variations among these platforms, the core concepts remain the same. One notable challenge is the absence of a Python-based quantum interpreter to connect these five frameworks, a gap that remains to be fully addressed. In response, our work introduces a tool called Qinterpreter, accessible through a user-friendly web interface, the Quantum Science Gateway QubitHub, which operates alongside Jupyter Notebooks. Built using the Python Object-Oriented Programming System, Qinterpreter unifies the five well-known quantum libraries into a single framework. Designed as an educational tool for students and researchers entering the quantum domain, Qinterpreter enables the straightforward development and execution of quantum circuits across such platforms. This work highlights the quantum programming versatility and accessibility of Qinterpreter and underscores our ultimate goal of pervading Quantum Computing through younger, less specialized, and diverse cultural and national communities.